2013
DOI: 10.1038/nature12144
|View full text |Cite
|
Sign up to set email alerts
|

Receptor binding by a ferret-transmissible H5 avian influenza virus

Abstract: Cell-surface-receptor binding by influenza viruses is a key determinant of their transmissibility, both from avian and animal species to humans as well as from human to human. Highly pathogenic avian H5N1 viruses that are a threat to public health have been observed to acquire affinity for human receptors, and transmissible-mutant-selection experiments have identified a virus that is transmissible in ferrets, the generally accepted experimental model for influenza in humans. Here, our quantitative biophysical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
280
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(307 citation statements)
references
References 29 publications
23
280
3
1
Order By: Relevance
“…This particular H5 mutant hemagglutinin binds the human α2,6-linked receptor in the same binding pattern (cis conformation) as seen for the HAs of previously reported 1957 and 1968 pandemic infl uenza viruses, which warrants further assessment in the future in order to prevent any possible pandemic caused by H5N1 subtype of avain infl uenza virus. During the preparation of this manuscript, two similar results have been reported in top journals (Xiong et al, 2013;Zhang et al, 2013), indicating this research is really a hot area.…”
Section: Thermostability Measurements Using Circular Dichroism (Cd)supporting
confidence: 66%
“…This particular H5 mutant hemagglutinin binds the human α2,6-linked receptor in the same binding pattern (cis conformation) as seen for the HAs of previously reported 1957 and 1968 pandemic infl uenza viruses, which warrants further assessment in the future in order to prevent any possible pandemic caused by H5N1 subtype of avain infl uenza virus. During the preparation of this manuscript, two similar results have been reported in top journals (Xiong et al, 2013;Zhang et al, 2013), indicating this research is really a hot area.…”
Section: Thermostability Measurements Using Circular Dichroism (Cd)supporting
confidence: 66%
“…23). The different outcomes could be due to the different receptor-binding properties of the H5N1 and H7N9 viruses 15,[24][25][26][27][28][29][30][31][32] . The H5N1 viruses display strong binding to avian receptors and weak binding to human receptors, and sporadically infect humans.…”
Section: Discussionmentioning
confidence: 99%
“…1). We also determined the structures of H5.3 in complex with H5hd containing the rdt mutations from the Kawaoka (H5hd_rdt_Vn, PDB ID code 4XNQ) and Fouchier (H5hd_rdt_In, PDB ID code 4XRC) laboratory strains to 2.15 Å and 2.74 Å, respectively (18,23). Refinement and data quality statistics are given in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Receptor specificity is critically influenced by position 226 on HA; Gln226-containing H3 strains are specific for α2,3 sialic acid linkages, and Leu226-containing H3 strains are specific for α2,6 sialic acid linkages (5, 16). In H5 strains, Leu226 enhances binding to α2,6-linked sialic acid receptors, but H5 viruses isolated from humans contain mutations at other sites that also promote use of α2,6-linked sialic acid receptors (11,17,18). Recent influenza pandemics have been caused by the acquisition of mutations that change the receptor preference to α2,6 sialic acid linkages, and recent studies with multiply passaged laboratory strains indicated that only a small number of mutations are necessary to introduce preference for α2,6 linkages into H5 strains (1, 6-9, 18-23).…”
mentioning
confidence: 99%
See 1 more Smart Citation